Konseling Kelompok Siswa Kesulitan Belajar Spesifik di Sekolah Dasar Inklusi - Dita Padiani Rahma; Tita Rosita (Quanta : Jurnal Kajian Bimbingan dan Konseling dalam Pendidikan, 2024)
The purpose of this study is to examine the role of counseling in helping to solve various problems of students with specific learning difficulties in inclusive elementary schools. Specific learning difficulties are neurobiological disorders that cause children to have difficulties covering academic aspects such as reading, writing and counting skills. The research method used is qualitative research with a literature study approach. Based on the results of the research obtained data that children with specific learning difficulties consist of three types, namely (1) dyslexia, (2) dysgraphia, and (3) dyscalculia. The impact of specific learning difficulties is low academic scores, low self-esteem, decreased motivation to learn, and unstable emotions. So that counseling for children with specific learning difficulties is to help problems with some of the effects of these difficulties, with the aim that children are able to learn optimally at school. The counseling techniques used are cognitive group counseling, reality counseling, Individualized Education Program (IEP) counseling, and Solution-Focused Brief Therapy (SFBT) counseling.